2022
DOI: 10.1155/2022/5106036
|View full text |Cite
|
Sign up to set email alerts
|

Digitized Visual Transformation of Grotto Art Using Deep Learning and Virtual Reality Technology

Abstract: The purpose is to convert the contents of the grotto murals into a digital vision based on deep learning (DL) and virtual reality (VR) technology to protect the precious grotto murals. The grotto murals are analyzed and modeled by introducing the related concepts of the digital library, using VR technology, and taking the cultural relics data acquisition technology as the basic framework. Then, the cultural relics information collection technology under DL is combined with VR technology, the color and material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Using computer technology, digitally repaired damaged murals can be helpful for the virtual display of the murals, and it has been shown that cloud edge computing could be a useful tool to automatically identify and repair the cracks of murals [ 136 ]. Deep learning and visual reality technology can build a digital recognition model which can accurately identify the colors and drawing materials of each specific color and thus be of great significance for the preservation simulation of murals [ 137 , 138 ]. However, deep learning methods usually require a large amount of data and computational resources.…”
Section: Measures For Mural Restoration and Protectionmentioning
confidence: 99%
“…Using computer technology, digitally repaired damaged murals can be helpful for the virtual display of the murals, and it has been shown that cloud edge computing could be a useful tool to automatically identify and repair the cracks of murals [ 136 ]. Deep learning and visual reality technology can build a digital recognition model which can accurately identify the colors and drawing materials of each specific color and thus be of great significance for the preservation simulation of murals [ 137 , 138 ]. However, deep learning methods usually require a large amount of data and computational resources.…”
Section: Measures For Mural Restoration and Protectionmentioning
confidence: 99%
“…In the requested that IT is used in education on a constant basis to enhance the calibre of instruction in recent years [11]. In practical teaching, the flipped classroom model and art teaching resource database were widely used, and some outcomes were seen [12]. It showed the potential benefits of utilizing novel online psychometric tools for students' psychological counselling, opening up fresh possibilities for digital art teaching platform to help students' psychological needs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional single-disciplinary perspectives and research methods, this paper employs information technology tools to provide a wide range of perspectives, frameworks, and examples from the perspective of cultural and ritual criticism, and to ponder how to integrate art and technology to perpetuate and pass on the excellent genes in traditional art. The integration of art and information technology will bring opportunities to traditional art research, as exemplified by Kouretsis et al[114], Xie[115] and Liu et al[116], and others. This paper promotes interdisciplinarity in the arts.…”
mentioning
confidence: 99%